New perspectives on the evolution of exaggerated traits. (19th December 2012) - Shingleton, Alexander W.; Frankino, W. Anthony
Abstract The scaling of body parts is central to the evolution of morphology and shape. Most traits scale proportionally with each other and body size such that larger adults are essentially magnified versions of smaller ones. This pattern is so ubiquitous that departures from it – disproportionate scaling between trait and body size – pique interest because it can generate dramatically exaggerated traits. These extreme morphologies are frequently hypothesized to result from sexual selection and their study has a long history, with several hypotheses seeking to explain their evolution. Despite this effort, surprisingly little progress has been made in demonstrating the forms of selection that produce different scaling patterns or in identifying the mechanisms that underlie the expression and evolution of scaling relationships. Here we review recent insights regarding the proximate mechanisms that regulate and integrate trait growth and that offer a new framework for studying the evolution of morphological scaling.